INTRA-SPESIFIC DIVERSITY OF BUTTERFLY PEA (Clitoria ternatea L.) REVEALED BY ISSR WITH INVARIABLE ITS RECORDS - Adib Fakhruddin Yusuf; Vida Rahma Latifah; Vivi Indah Nurcahyati; Anggun Diyan Nurhasanah; Adristi Shafa Widyasari; Ananto Puradi Nainggolan; Aldy Riau Wansyah Hasibuan; Madyan Akmal Hidayat; Karmilah Karmilah; Arini Dian Pratiwi; Rindu Aurantika; Muslifah Hasanah; Ganies Riza Aristya; Niken Satuti Nur Handayani; Tuty Arisuryanti; Indra Lesmana; Budi Setiadi Daryono (BIOTROPIA, 2025)
Article Highlights:- The ITS region exhibits no genetic variation among butterfly pea genotypes.- ISSR reveals high polymorphism, proving effective for genetic diversity analysis.- White single and purple single genotypes show the greatest genetic distance.- ISSR-6 ((CT)₈TG) demonstrates the highest polymorphism and reliability for assessment.- The ITS sequences have been deposited in GenBank under the accession IDs PQ198055–PQ198061. ABSTRACTClitoria ternatea L., a perennial plant in the Fabaceae, is recognized for its resilience in tropical climates and its diverse applications in both culinary and medicinal fields. However, the limited exploration of its genetic diversity constrains breeding efforts aimed at improving desirable traits. This limitation highlights the need to optimize selection strategies, identify superior genotypes, and preserve valuable genetic resources for long-term conservation and crop enhancement. This study aimed to explore genetic variation using molecular markers to analyze C. ternatea genotypes based on petal architecture and color differences. To assess the genetic diversity of C. ternatea, Sanger sequencing of the Internal Transcribed Spacer (ITS) region and Inter-Simple Sequence Repeat (ISSR) markers were applied to seven wild populations from Sleman, Yogyakarta. The ITS region exhibited no genetic variation, indicating its conserved nature and limited ability to differentiate genotypes. In contrast, ISSR markers effectively detected genetic variation, identifying 62 polymorphic fragments out of 162 total bands. The highest genetic distance (0.297) was observed between the WS and PS genotypes, whereas the double-petal genotypes (WD and PD) displayed the closest phenetic relationship. Among the ISSR primers, UBC-808, UBC-812, and ISSR-6 exhibited high PIC and RP values, confirming their reliability in genetic diversity analysis. These results underscore the utility of ISSR markers as a robust tool for genetic diversity assessment, offering valuable insights for breeding programs and germplasm conservation in C. ternatea.